The Personality Of Tifani Fanelli In Jessica Knoll’s Novel Luckiest Girl Alive - Intan Tangngi Rapa; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
This study aimed to discover the personality and factors that influence TifAni FaNelli’s personality development in Jessica Knoll’s novel Luckiest Girl Alive. The data sources used in this study was novel Luckiest Girl Alive by Jessica Knoll. In analysing the data, the writer used descriptive qualitative method through psychology approach. Data were obtained by using the techniques of reading, noting, and analysing. Meanwhile in classifying the data, the writer used Adler’s Individual Psychology theory. The research reveal that the novel  contained personalities of easily influenced, a liar, patient, innocent, obsession, a dreamer,  forgiving,  lack of confidence, loyal, jealousy, generous, trendy, emotional, and brave. While data that included factors, inferiority are, social interest, fictional final goal. So,  the dominants personality were easily influenced, obsession, emotional, and inferiority factor.